Mechanisms and Dynamics of Protein Acetylation in Mitochondria. Issue 3 (March 2016) - Baeza, Josue; Smallegan, Michael J.; Denu, John M.
Abstract : Reversible protein acetylation is a major regulatory mechanism for controlling protein function. Through genetic manipulations, dietary perturbations, and new proteomic technologies, the diverse functions of protein acetylation are coming into focus. Protein acetylation in mitochondria has taken center stage, revealing that 63% of mitochondrially localized proteins contain lysine acetylation sites. We summarize the field and discuss salient topics that cover spurious versus targeted acetylation, the role of SIRT3 deacetylation, nonenzymatic acetylation, and molecular models for regulatory acetylations that display high and low stoichiometry. Trends: Improvements in mass-spectrometry-based proteomics have uncovered protein acetylation as a prominent post-translational modification, and the latest methods report fold-change and stoichiometry. Mitochondria appear to harbor a disproportionately high number of acetylated proteins. Mitochondrial acetylation is thought to be largely non-enzymatic, mediated by reactive lysine residues and acetyl-CoA. The NAD + -dependent deacetylase SIRT3 removes mitochondrial acetylation, and loss of SIRT3 function is linked to increased ROS and altered oxidative metabolism. Protein acetylation in mitochondria typically leads to loss of function in pathways associated with organelle integrity and oxidative metabolism. Additional endogenous lysine acylations (e.g., succinylation, glutarylation) occur and can be catalytically removed by members of the sirtuin family.